Clusterin facilitates COMMD1 and I-κB degradation to enhance NF-κB activity in prostate cancer cells - Zoubeidi, Amina; Ettinger, Susan; Beraldi, Eliana; Hadaschik, Boris; Zardan, Anousheh; Klomp, Leo W.J.; Nelson, Colleen C.; Rennie, Paul S.; Gleave, Martin E. (Molecular cancer research)
Secretory clusterin (sCLU) is a stress-activated, cytoprotective chaperone that confers broad-spectrum cancer treatment resistance, and its targeted inhibitor (OGX-011) is currently in phase II trials for prostate, lung, and breast cancer. However, the molecular mechanisms by which sCLU inhibits treatment-induced apoptosis in prostate cancer remain incompletely defined. We report that sCLU increases NF-κB nuclear translocation and transcriptional activity by serving as a ubiquitin-binding protein that enhances COMMD1 and I-κB proteasomal degradation by interacting with members of the SCF-βTrCP E3 ligase family. ...